Специфіка надання податково-консультаційних послуг в державах Східноєвропейського регіону - Повар, Віталій Олександрович; Povar, Vitaliy Oleksandrovych (Ірпінь, 2023)
Магістерське дослідження розглядає динаміку з’ясування історії становлення, розвитку та сучасного стану податково-консультаційних послуг в державах Східноєвропейського регіону і визначення шляхів використання їх досвіду в Україні. За результатами дослідження сформульовані висновки щодо перспектив розвитку ринку податково-консультативних послуг в Україні на прикладі країн східноєвропейського регіону.

The master's study examines the dynamics of clarifying the history of the formation, development and current state of tax consulting services in the countries of the Eastern European region and determining ways of using their experience in Ukraine. Based on the results of the research, conclusions are formulated regarding the prospects for the development of the market of tax advisory services in Ukraine using the example of the countries of the Eastern European region.
The specifics of the provision of tax consulting services in the countries of the Eastern European region
Keywords: податково-консультативні послуги; палати податкових консультантів; країни східноєвропейського регіону; tax advisory services; chambers of tax consultants; countries of the Eastern European region